Aspirin Prophylaxis in Chronic Paroxysmal Hemicrania - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
A nine year old child with chronic paroxysmal hemicrania (CPH) was treated successfully using small dose aspirin prophylaxis at the California Medical Clinic for Headache, Encino, and the Harbor-UCLA Medical Center, Torrance, CA.